If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6+3/2x=9
We move all terms to the left:
6+3/2x-(9)=0
Domain of the equation: 2x!=0We add all the numbers together, and all the variables
x!=0/2
x!=0
x∈R
3/2x-3=0
We multiply all the terms by the denominator
-3*2x+3=0
Wy multiply elements
-6x+3=0
We move all terms containing x to the left, all other terms to the right
-6x=-3
x=-3/-6
x=1/2
| –12+6g+13g=19g−12 | | m+3.89=9.02 | | 8(–3g+4)=8g | | -24k+3.6=-7.8 | | p-11=16 | | 4x+13=5x-15(x-9) | | z-1.8=2.3 | | 5b+12+b=60 | | 4x+13=5x-15x-9 | | −7x+2+3x=−38 | | -4(5+7)+11x=x+4 | | 5p=7(5p+6) | | z-2.3=1.8 | | -2.4k+3.5=-7.8 | | 5e+30=75 | | −7+7x−3x=37 | | (3)/(4x-5)=x | | 3p-20=100 | | z-1/7=4/7 | | 5x+8=324 | | 2.5x+0.4=7.9 | | -9(9-5n)+n=4n+71 | | x+6=3x | | 48÷x=-8 | | -6(n+1)=30 | | 25^1/2x5-3=5x | | x.36.4=4x | | y-5.45=7.83 | | -5+8x+4x-10=225 | | -0.375c-11=1 | | y+4.3=20 | | (x^2-x)^2=12+4x-4x^2 |